Estudo da apocinina e diapocinina e seus derivados de chalconas como antioxidante e antibacterianos potenciais: síntese, avaliação da ação antibacteriana, antioxidante e das propriedades físico-químicas - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The apocynin is an acetophenone which has little structure and has several biological activities. Its structure can be oxidized in certain chemical or biological conditions and result in the formation of the dimer, the diapocinina. The chalcones are compounds containing in its basic structure portion 1,3-diaryl-pro-2-en-1-one and are characterized by having variety of biological activities such as antibacterial and antioxidant activity. Studies show that structural modifications on the aromatic rings of chalcones result in obtaining the compounds with acceptor radical and antibacterial activity. In this work were performed chalcones derived synthesis of apocynin and diapocinina, the evaluation of antioxidant and antimicrobial activity. It was also performed molecular modeling studies, determination of physicochemical properties and toxicity evaluation in silico, in order to obtain compounds which can be used as prototypes of new drugs. The derivatives of the chalcones and apocynin diapocinina, substituents 4-OCH3, 3,4-OCH3, and 3,4,5-OCH3 attached to B ring, unsubstituted (H) were synthesized by Claisen-Schmidth condensation, of benzaldehydes with apocynin and diapocinina, in basic medium at room temperature for 24 hours. After each reaction, the compounds were analyzed and purified by recrystallization or column chromatography. The compounds were characterized by TLC, melting point, infrared spectroscopy (IR) and 1H and 13C NMR. The acceptor capacity analysis of radical synthesized molecules were carried out by employing the colorimetric method of analysis of DPPH and ABTS using standard as BHT and Trolox, respectively, at concentrations 6.75, 12.5, 25, 50, 100 200 and 400 uM. The evaluation of the antibacterial activity of the obtained compounds was performed by the method of agar-cylinder diffusion and reading inhibition zones, where Staphylococcus aureus ATCC 25923 (Gram positive bacterium) and Escherichia coli ATCC 25922 (Gram negative bacteria) were tested using as standard antibiotic chloramphenicol. The analysis of in silico toxicity, such as genotoxicity, mutagenicity, and irritating effects on reproductive system, was performed using the computer program Osiris Property Explorer. The compounds showed acceptor activity of DPPH and ABTS radical in the concentration range of 400 to 12,5μM, being superior to the standard of BHT and Trolox. The evaluation of the antibacterial activity test all compounds showed antibacterial activity against Staphylococcus aureus strain being, however, lower than the standard chloramphenicol. There was no activity against Escherichia coli strain. From the analysis of in silico toxicity it was observed that only compounds which had OCH3 groups substituted in the para position, exhibited medium and high risk of irritating and toxic effect on the reproductive system. Other compounds showed low theoretical risk of developing toxic effects reported. Considering the results, it is observed that the derivatives of apocynin and diapocinina chalcones present as promising compounds for the study and development of agents having antioxidant activity, antibacterial action and low theoretical toxicity, thus demonstrating potential agents for use in therapy.
Study and apocynin diapocinina and its derivatives chalcones as antioxidant and antibacterial potential: synthesis, antibacterial action assessment, antioxidant and physical and chemical properties
Keywords: Apocinina; Diapocinina; Chalconas; Antioxidantes; Antibacterianos; Apocynin; Diapocinina; Chalcones; Antioxidants; Antibacterial